Correlation of epidermal growth factor receptor score with prognostic variables in transitional cell carcinoma of urinary bladder among north-eastern Indian population - Barua, Sasanka Kumar; Das, Nabajeet; Baruah, Saumar Jyoti; P., Rajeev T.; Bagchi, Puskal Kumar; Sarma, Debanga; Phukan, Mandeep (International Surgery Journal, 2018)
Background: Epidermal growth factor receptor (EGFR) has demonstrated over expression in bladder tumours and correlation with stage and grade of tumours. The aim of present study was to find the relation between score of the EGFR in Transitional Cell Carcinoma (TCC) of bladder and its various prognostic variables. Methods: This is a retrospective study conducted in Dept of Urology, Gauhati Medical College Hospital between Dec 2016 and July 2017. Forty cases of TCC bladder that were operated either by TURBT or radical cystectomy have been taken. However, patients with CKD, pre-existing systemic disease and UTI were excluded from the study. Presence of EGFR and its score were analysed. The rating was done as 0 (non-immunoreactive), 1+ (weak), 2+ (moderate) and 3+ (strong). The correlation between EGFR score and the various factors like age, sex, stage, size of tumour, presence of CIS, tumour grade, muscle invasion, number of tumours and type of stalk were evaluated statistically using chi square tests. Results: Average age is 59.825 years and male to female ratio is 5.6:1. EGFR score is not significantly related with age, sex, stage of disease, muscle invasiveness or number of tumours whereas size of tumour, presence of CIS changes, grade of TCC and type of tumour stalk bears statistically significant relation with EGFR score. Conclusions: Studies have shown EGFR positivity to be associated with high tumour stage, tumour progression, and poor clinical outcome. Authors have found size >3cm, CIS changes, high grade tumours and broad-based stalks to be significantly associated with higher EGFR scores among patients with TCC of bladder.